Preparation of monoclonal antibodies to xanthine oxidase and other proteins of bovine milk-fat-globule membrane. - Mather, I H (1980)
Nine hybridomas secreting monoclonal antibody to proteins of bovine milk-fat-globule membrane were isolated. All nine cell lines continued to secrete monoclonal antibody after serial transfer in culture and after passage as solid tumours in Balb/cJ mice. Four of the cell lines secreted monoclonal antibody specific for xanthine oxidase, one of the major proteins of milk-fat-globule membrane.